Analysis and design of an isolated three-phase micro inverter with integrated energy storage - Brandão, Felipe da Cunha (2023)
In order to achieve the decarbonization targets and to combat climate change, it is necessary to reduce the use of fossil fuels and increase energy production from renewable sources. Due to being silent, easy to install and maintain, photovoltaic (PV) systems have experienced great growth over the last few years. The microinverter, as the interface between the PV array and the power grid, has become increasingly popular due to its potential to achieve high reliability, individual power optimization and provide considerable system flexibility. Within this context, this work presents a two-stage and three-port microinverter for photovoltaic applications operating connected to the three-phase electrical grid (three-wire). One port accommodates the photovoltaic panel, the other port accommodates a storage system and the third port is connected to the conventional electrical network. The energy storage system (which can be a battery or supercapacitor) operates as a backup source to compensate for energy fluctuations and store excess energy generated by the photovoltaic panel. A Dual Active Bridge (DAB) converter is used to provide galvanic isolation and maximum power point tracking of the photovoltaic panel. The inverter connected to the grid is a Voltage Source Inverter (VSI). Tests are performed on the system controlling the VSI with different strategies ranging from the classical linear approach to the Model Predictive Control - MPC. The aim is to evaluate the influence of the strategies on the THD of the output current. An analysis of the influence of the parametric variation of the circuit on the THD is also carried out. The studies were carried out by computer simulations considering a 400W microinverter.